Creating person-centred support for people with intellectual disabilities at the end of life: An Australian qualitative study of unmet needs and strategies. (December 2020) - McNamara, Beverley; Same, Anne; Rosenwax, Lorna
Background: People with intellectual disabilities at the end of life are at risk of receiving inadequate and inequitable end-of-life care. This study explores their unmet needs, opportunities for person-centred care and experiences of health service use. Methods: Qualitative interviews with 26 experienced health professionals and carers were used to explore their patients' and residents' unmet needs and end-of-life care options and to outline strategies to support them. Results: A range of challenges and unmet needs experienced by people with intellectual disabilities are presented in themes: (1) accommodation setting at the end of life: dying 'at home'; (2) personal factors and networks: a circle of support; (3) end-of-life medical care and decision-making. Strategies to facilitate good end-of-life care and a model of care are presented. Conclusions: Well-prepared and collaborative disability and health service workforces are needed, together with flexible and adequate end-of-life funding to ensure compassionate and person-centred care.